Hedonic Happiness of Foreign Tourists in Bali - Ariana, Nyoman; Antara, Made; Budiarsa, Made; Sudiarta, Nyoman (Journal of Indonesian Tourism and Development Studies, 2021)
There are many reasons why tourists travel or visit certain places, and chief among them is to seek happiness. For example, they feel happy when they get the hedonic experience. Unfortunately, the effect of hedonic values and tourism experiences on tourists' happiness has thus far remained unclear. This study was aimed to analyze the effect of hedonic value on the tourist experience, prove the effect of hedonic value on tourists' hedonic happiness, and examine the effect of tourist experience on tourists' hedonic happiness. This research took place in Bali, and the research subjects were foreign tourists who visited Bali. The total number of respondents was 171. All structured interviews and questionnaires were performed and distributed online. Data analysis was conducted using SEM (Structural Equation Model). The research findings show the positive and significant effect of hedonic values on tourist experience. There is a positive and significant effect of tourist experience on tourist hedonic happiness. It was found that there was no direct effect of hedonic value on tourist hedonic happiness. Out of the demonstrated intervariable correlations, we managed to create the Model of Hedonic Tourist Happiness (MHTH). This study concludes that the MHTH consists of hedonic value, tourist experiences, and tourist hedonic happiness variables. This MHTH can be applied to improve tourism services in Bali, and particularly to boost the tourist experience and tourist happiness. Keywords: Bali, Hedonic Happiness, Tourists Experiences.